Studi Kasus Penerapan Discharge Planning Terstruktur Pada Pasien Post Appendiktomi - tai tuba, maria rosamistika; Meo, Maria Yulita (Jurnal Ilmiah Wahana Pendidikan, 2024)
Discharge planning is an effor made from the moment the patient arrives at the hospital until the patient is scheduled to go hom to increase the patient’s knowledge about the concept of disease, diet, activity patterns and pharmacology that must be continued at home. The aim of this case study is to explain how to implementing of structured discharge planning in post Appendectomy patients in the Dahlia Room BLUD RSUD dr. T.C. Hillers Maumere. Research method: using descriptive methods with a case study approach. The results of the SWOT analysis show that the implementation of discharge planning in the Dahlia Room at dr. Tc. Hillers Maumere Regional Hospital obtained an IFAS value of -0,7, while the EFAS value was 1. The mapping results in the Flyover Diagram show that the implementation of discharge planning is in the WO quadrant, so the strategic steps that need to be taken are progressive, which means that the internal weaknesses of the Dahlia Room at RSUD BLUD dr.Tc.Hillers Maumere need to be improved to get more external opportunities.